Characterization technique for detection of atom-size crystalline defects and strains using two-dimensional fast-Fourier-transform sampling Moiré method. (14th March 2018) - Kodera, Masako; Wang, Qinghua; Ri, Shien; Tsuda, Hiroshi; Yoshioka, Akira; Sugiyama, Toru; Hamamoto, Takeshi; Miyashita, Naoto
Abstract: Recently, we have developed a two-dimensional (2D) fast-Fourier-transform (FFT) sampling Moiré technique to visually and quantitatively determine the locations of minute defects in a transmission electron microscopy (TEM) image. We applied this technique for defect detection with GaN high electron mobility transistor (HEMT) devices, and successfully and clearly visualized atom-size defects in AlGaN/GaN crystalline structures. The defect density obtained in the AlGaN/GaN structures is ∼10 13 counts/cm 2 . In addition, we have successfully confirmed that the distribution and number of defects closely depend on the process conditions. Thus, this technique is quite useful for a device development. Moreover, the strain fields in an AlGaN/GaN crystal were effectively calculated with nm-scale resolution using this method. We also demonstrated that this sampling Moiré technique is applicable to silicon devices, which have principal directions different from those of AlGaN/GaN crystals. As a result, we believe that the 2D FFT sampling Moiré method has great potential applications to the discovery of new as yet unknown phenomena occurring between the characteristics of a crystalline material and device performance.